Estimation of the glomerular filtration rate in older individuals with serum creatinine-based equations: a systematic comparison between CKD-EPI and BIS1 - Oscanoa, Teodoro J. (2018)
Aim: CKD-EPIcr (Chronic Kidney Disease Epidemiology Collaboration creatinine) and BIS1 (Berlin Initiative Study) are two serum creatinine-based formulae for the estimation of glomerular filtration rate (GFR). However, their comparative accuracy in older people has not been well established. Our aim was to conduct a systematic comparative study of the accuracy of estimation of GFR in older people with these two formulae. Methods: We conducted a systematic search in Pubmed, EMBASE and Central databases on the validity of the CKD-EPIcr and BIS1 formulae in people aged 60 or more years. The search ranged from 2009 and 2012 for CKD-EPIcr and BIS1, respectively, until May 2017. The validity criterion for comparing the formulae was to have a P30 accuracy level equal to or greater than 80%. Results: Of 1295 identified studies, 16 met our inclusion criteria. Out of 16 studies reporting the accuracy of the CKD-EPIcr formula, only 5 (31.3%) had P30 scores ≥80% (mean P30 was 77.1 ± 7.711 range 55.5-91.7), and out of 9 studies on accuracy using the BIS1 formula, 6 (66.7%) were ≥80% (mean P30 was 83.88 ± 9.37, range 67.0-95.8). Conclusion: Our results suggest that for the estimation of the GFR in older people, BIS1 formula may be more accurate than CKD-EPIcr.